ASESMEN KINERJA PEGAWAI BADAN NARKOTIKA NASIONAL PROVINSI SULAWESI TENGGARA DALAM MENANGGULANGI PEREDARAN NARKOBA DI MASYARAKAT - Darmin Tuwu (Institut Agama Islam Negeri Kendari, 2019)
This study lays out performance assessments of sixteen personnels from the Community Prevention and Empowerment Division of the National Narcotics Agency of Southeast Sulawesi Province in counterbalancing drug abuse and traffic within society. It is a case study with qualitative approach. The data were obtained through in-depth interviews and observations. This study proves out personnels’ performance to be classified as `good`. According to the assessment scores which were identified by the number 1 to 5, most of the personnels scored 3 (good enough), 4 (good), and 5 (very good). These scores were taken from five criteria of personnel's performance being assessed that includes the performance quality, personnel’s initiatives, and their communication skills. Those three criteria were so prominent that the overall performance quality of Community Prevention and Empowerment Division personnels can be classified as